An assessment of a GMP schistosomiasis vaccine (SchistoShield®) - Kim, Jiho; Davis, Jenn; Lee, Jinhee; Cho, Sang-Nae; Yang, Kiyoung; Yang, Jaekyoon; Bae, Sungmin; Son, Joohee; Kim, Boyoung; Whittington, Dale; Siddiqui, Afzal A.; Carter, Darrick; et al. (Frontiers in Tropical Diseases, 2024)
IntroductionSchistosomiasis is a neglected tropical disease that puts over 200 million people at risk, and prevention options are sparse with no approved vaccine. Our vaccine candidate, SchistoShield®, is based on an approximately 87 kDa large subunit of calcium activated neutral protease - termed Sm-p80 - combined with a potent TLR4 agonist-based adjuvant. SchistoShield® has been shown to prevent disease throughout the parasitic life cycle - including egg, juvenile, and adult worm stages - in numerous animal models up to and including baboons. SchistoShield® has been shown safe in both preclinical toxicology studies in rabbits and in a Phase 1 clinical trial in the USA. A Phase 1b trial was initiated in 2023 in endemic regions of Africa, and to date no serious safety signals have been reported.MethodsIn preparation for large-scale Phase 2 clinical trials and eventual vaccine deployment, the Sm-p80 antigen production process has been transferred to a manufacturing organization, Quratis Corporation in South Korea, which specializes in preparation of vaccines for large-scale European and African trials. The process of scaling from our current production level of ~ 2000 vaccine doses, to a process that will generate more than 100 million doses has required multiple improvement steps in the process including fermentation, downstream purification of the protein antigen, lyophilization, and fill and finish.ResultsIn this study, we detail the large-scale production process of the SchistoShield® protein product by Quratis. In addition, an effort was made to analyze and compare the Quratis-made lot of Sm-p80, referred to as QTP-105, to the cGMP lot of Sm-p80 which is in use in human trials in the USA and Africa, referred to as Sm-p80 DP (made in USA). We show that QTP-105 demonstrates excellent potency, purity, identity, and endotoxin levels compared to our Phase 1 Sm-p80 DP and is suitable for use in Phase 2 studies and beyond.